First Record of Psorospermium sp. (Class: Mesomycetozoea) in Northern Clearwater crayfish Faxonius propinquus Girard 1852 (Decapoda: Cambaridae) from Michigan, U.S.A. - Anaya, Christina (Zootaxa, 2021)
Psorospermium cf. haeckeli Hilgendorf 1883 is a unicellular, eukaryotic protozoan within the class Mesomycetozoea, phylogenetically situated near the animal-fungal divergence(Cavalier-Smith 1998; Ragan et al. 1998). Although only one species has been identified, there have been four morphotypes described in 17 species of crayfish from the Holarctic, Neotropical, and Australasian regions (Herbert 1987; Henttonen et al. 1992, 1994; Rug & Vogt 1994). However, molecular analyses of the internal transcribed spacer DNA suggest morphotypes may represent distinct species (Bangyeekhun et al. 2001).